Poly Cystic Ovarian Syndrome: An Updated Overview - El Hayek, Samer; Bitar, Lynn; Hamdar, Layal H.; Mirza, Fadi G.; Daoud, Georges (Frontiers in Physiology, 2016)
1. Abstract Poly Cystic Ovarian Syndrome (PCOS) is one of the most common metabolic and reproductive disorders among women of reproductive age. Women suffering from PCOS present with a constellation of symptoms associated with menstrual dysfunction and androgen excess, which significantly impacts their quality of life. They may be at increased risk of multiple morbidities, including obesity, insulin resistance, type II diabetes mellitus, cardiovascular disease, infertility, cancer, and psychological disorders. This review summarizes what the literature has so far provided from guidelines to diagnosis of PCOS. It will also present a general overview about the morbidities associated with this disease, specifically with its more severe classic form. Finally, the review will stress on the various aspects of treatment and screening recommendations currently used in the management of this condition.